A multidisciplinary design approach for electromagnetic brakes - Yasa, Yusuf; Sincar, Eyyup; Ertugrul, Baris Tugrul; Mese, Erkan (ELSEVIER SCIENCE SA, 2016)
The design of an electromagnetic brake requires a multidisciplinary approach. Its performance is a field of interest having implications for mechanical, electrical, magnetic and material engineering. In this study, a comprehensive design procedure for the electromagnetic brake is presented. Simple and effective mechanical and thermal models are derived analytically and numerically. The analytical model is developed to optimize the coil turns, conductor radius and airgap length with the combination of input current and voltage. Candidate magnetic materials are discussed in terms of minimizing the cost while meeting electromagnetic performance characteristics. Simulation and experimental tests are conducted on a prototype of brake to verify the design. Good agreement between the test results and the prototype is achieved. Some differences are found and their root causes are investigated. Symptoms about parallelism in brake can be directly understood from the current waveform which enables to measure tolerances and to identify the problems of the brake at an early phase. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Brake; Electric release brake; Electromagnetic; Electromechanical brake; Servo applications; Servo motor brake; Spring applied brake; Engineering